KUALITAS PELAYANAN UNIT PELAKSANA TEKNIS PERPUSTAKAAN PUSAT UNIVERSITAS SLAMET RIYADI SURAKARTA - Damayanti Suhita, Farco Siswiyanto Raharjo, Qomaruddin & (Transformasi, 2017)
This research has qualitative descriptive nature to describe how service quality in the TechnicalImplementation of Central Library in Slamet Riyadi University. Use the interactive analysis. Theresults showed that service users rate thatb the quality of service of Central Library in SlametRiyadi University through several aspects include confidence, reliability, responsiveness,concern, and intangibles.Key words: quality, service, library